BURUH PEREMPUAN DI TENGAH KUBANGAN PARA KORUPTOR - Triana Sofiani (Muwazah, 2012)
Abstract : The Center of hegemony, which is built on the common valuesÂ  common interests between the rulers and capitalists who incidentally are in the sex of "males", makes women workers turn out to be worse in the encirclement of the corruptors. In fact, corruption that is rampant in this country, become a series of chains of the impoverishment of women workers, therefore women workers are affected by the domino effect as caused by the corrupts. Hence, the real movement against corruption on the basis of the women becomes an urging agenda to be realized immediately, in order to give effective contribution as linked to the rampant corruption in the country and also its impact on women workers. Abstrak : Pusat hegemoni, yang dibangun di atas nilai-nilai umum kepentingan bersama antara penguasa dan kapitalis yang notabene berada di jenis kelamin "laki-laki", membuat pekerja perempuan berubah menjadi lebih buruk dalam pengepungan dari para koruptor. Bahkan, korupsi yang merajalela di negeri ini, menjadi serangkaian rantai pemiskinan pekerja perempuan, oleh karena itu pekerja perempuan dipengaruhi oleh efek domino yang disebabkan oleh korup. Oleh karena itu, gerakan nyata melawan korupsi atas dasar perempuan menjadi agenda mendesak untuk segera diwujudkan, untuk memberikan kontribusi yang efektif terkait dengan korupsi yang merajalela di negeri ini dan juga dampaknya terhadap pekerja perempuan.